A High‐Rate Aqueous Proton Battery Delivering Power Below −78 °C via an Unfrozen Phosphoric Acid. Issue 28 (8th June 2020) - Jiang, Heng; Shin, Woochul; Ma, Lu; Hong, Jessica J.; Wei, Zhixuan; Liu, Yusung; Zhang, Suoying; Wu, Xianyong; Xu, Yunkai; Guo, Qiubo; Subramanian, Mas A.; Stickle, William F.; et al.
Abstract: The sluggish ion diffusion and electrolyte freezing with volumetric changes limit the low‐temperature performance of rechargeable batteries. Herein, a high‐rate aqueous proton battery (APB) operated at and below −78 °C via a 62 wt% (9.5 m) H3 PO4 electrolyte is reported. The APB is a rocking‐chair battery that operates with protons commuting between a Prussian blue cathode and an MoO3 anode. At −78 °C, the APB full cells exhibit stable cycle life for 450 cycles, high round‐trip efficiency of 85%, and appreciable power performance. The APB delivers 30% of its room‐temperature capacity even at −88 °C. The proton storage mechanism is investigated by ex situ synchrotron XRD, XAS, and XPS. The APB pouch cells demonstrate no capacity fading at −78 °C, and thus offers a safe and reliable candidate for high‐latitude applications. Abstract : Aqueous proton battery (APB) full cells demonstrate outstanding low‐temperature performance via 62 wt% (9.5 m) H3 PO4 as the electrolyte that does not freeze until −85 °C. At −78 °C, the APB delivers negligible capacity fading over 450 cycles and high rate capability. The high‐performing pouch cells offer a safe and reliable option for polar and aerospace missions.